Capacity Building for English Teachers to Improve the Quality of Education in Schools - Church, Gordon S; Mardianto, Mardianto; Ibrahim, Abdul Aji (Universitas Islam Negeri Sumatera Utara, 2025)
Improving the quality of education in Indonesia, particularly in English language teaching, is crucial as English is key to addressing the challenges of globalization. In this context, the capacity of English teachers plays a vital role, as they are the primary link between students and the English language skills that open access to global resources. However, English language teaching in Indonesia faces various challenges, including inadequate facilities, competency mismatches among teachers, and limited access to continuous professional development. To address these challenges, this training program aims to enhance the capacity of English teachers by developing their pedagogical skills, deepening their understanding of subject matter, and integrating technology into English instruction. The program includes various activities, such as interactive workshops and online training, designed to introduce innovative teaching methods and improve the use of technology in the teaching and learning process. The expected outcome of these activities is an improvement in the quality of English teaching in Indonesia, which will in turn enhance students' English proficiency and better prepare them to compete at a global level. Additionally, with increased teacher capacity, the program is also expected to strengthen the reputation of schools and expand career opportunities for students in the future.